1998
DOI: 10.1007/s007050050346
|View full text |Cite
|
Sign up to set email alerts
|

Citrus viroid Ia is a derivative of citrus bent leaf viroid (CVd-Ib) by partial sequence duplications in the right terminal region

Abstract: Nucleotide sequences of group I citrus viroids Ia (CVd-Ia) and citrus bent leaf viroid (CBLVd, formerly designated CVd-Ib) isolated from citrus plants in Japan, the Philippines and China have been determined. Citrus samples in Japan and the Philippines contained CVd-Ia, which consists of 328 nucleotides(nt). Although 10 nt longer than the type CBLVd-225A in Israel they share 94% identity in overall nucleotide sequence. The Philippines sample also contained a 329-nt long CVd-Ia sequence variant, in which one ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…The vegetative reproduction of citrus trees in addition to the infected budwoods and top-grafting are the main factors which contribute to the high levels of mixed infections [ 54 ]. The importance of mixed infections is crucial, as they favor recombination events which play a significant role in viroids evolution [ 55 ] through the emergence of new viroids (e.g., CBCVd was created from recombination of CEVd and HSVd) [ 56 ] and strains with severe infectivity [ 57 , 58 ]. This may enhance symptom expression, leading to more damage [ 24 ] and importantly, expand their host range by the passage of viroids into new hosts in which they can be more catastrophic, similar to the case of CBCVd in hops [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The vegetative reproduction of citrus trees in addition to the infected budwoods and top-grafting are the main factors which contribute to the high levels of mixed infections [ 54 ]. The importance of mixed infections is crucial, as they favor recombination events which play a significant role in viroids evolution [ 55 ] through the emergence of new viroids (e.g., CBCVd was created from recombination of CEVd and HSVd) [ 56 ] and strains with severe infectivity [ 57 , 58 ]. This may enhance symptom expression, leading to more damage [ 24 ] and importantly, expand their host range by the passage of viroids into new hosts in which they can be more catastrophic, similar to the case of CBCVd in hops [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…CBLVd might be endemic in Asia Pacific region. Previous studies have shown that CBLVd was widely distributed in Asia Pacific region such as China, Japan, Malaysia, Pakistan and Philippines (Hataya et al 1998; Ito et al 2000; Cao et al 2009; Wu et al 2014; Khoo et al 2017). Results showed that CBLVd were detected in Citrofortunella microcarpa, C. aurantiafolia, C. hystrix, C. maxima and C. sinensis but not in C. reticulata .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the clones isolated from C. microcarpa, C. aurantiafolia, C. maxima and C. sinensis were identical and were defined as the consensus sequence of CVd-Ia which is a derivative of citrus bent leaf viroid (Formerly known as CVd-Ib). Therefore, based on the percentage sequence similarity, the CBLVd variant from citrus in Malaysia was determined as CVd-Ia (Hataya et al 1998; Ito et al 2002). In addition, sequence analysis showed that seven out of 12 clones obtained in this study had base substitution mainly occurred in Pathogenicity and Variable domain compared to CBLVd japan isolate.…”
Section: Discussionmentioning
confidence: 99%
“…CVd-Ib was later designated as citrus bent leaf viroid (CBLVd) (Ashulin et al 1991). Previous studies in Japan confirmed that CVd-Ia and CVd-I-LSS are related to CBLVd (Hataya et al 1998, Ito et al 2000. Currently, it is considered that CVd-Ia and CVd-I-LSS are also CBLVd variants .…”
Section: Citrus Viroids 1 Taxonomy and Strains (1) Recognition Of Cit...mentioning
confidence: 99%